2010
DOI: 10.1002/adsc.201000485
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Asymmetric Hydrogenation of Quinoline Derivatives with C3*‐TunePhos

Abstract: A series of C 3 *-TunePhos chiral diphosphine ligands has been successfully applied in the iridium-catalyzed enantioselective hydrogenation of quinolines, and this methodology provided an efficient access to a variety of optically active tetrahydroquinolines with up to 93% ee. Furthermore, attempts on the asymmetric hydrogenation of quinoline N-oxide are also discussed.Keywords: asymmetric catalysis; enantioselectivity; hydrogenation; iridium; quinolines The direct catalytic asymmetric hydrogenation of quinoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…As far as we know, few catalytic systems can be applied for asymmetric hydrogenation of both isoquinolines and quinolines with both high turn-overs and excellent enantioselectivities. 7 , 8 Then a question came to us: can this synthetic protocol be used to synthesize chiral THQs with high ee? By employing the optimized condition (DCM/iPrOH = 2 : 1, v/v) in the case of asymmetric hydrogenation of isoquinolines, we found that the enantioselectivity was dramatically increased to 99% ee.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as we know, few catalytic systems can be applied for asymmetric hydrogenation of both isoquinolines and quinolines with both high turn-overs and excellent enantioselectivities. 7 , 8 Then a question came to us: can this synthetic protocol be used to synthesize chiral THQs with high ee? By employing the optimized condition (DCM/iPrOH = 2 : 1, v/v) in the case of asymmetric hydrogenation of isoquinolines, we found that the enantioselectivity was dramatically increased to 99% ee.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, however, asymmetric hydrogenation of N-heteroaromatics, especially isoquinolines, remains a challenging task. 7 Although quinolines have been successfully hydrogenated in several cases, 8 there are only a few examples of isoquinolines. Zhou's group used an iridium–bisphosphine catalyst to obtain high enantioselectivity, but this transformation needs activation by chloroformate or the addition of BCDMH.…”
Section: Introductionmentioning
confidence: 99%
“…Later, in the study of the hydrogenation of N-aryl imines by Zhang and co-workers, iodine was chosen as the additive to promote this catalytic process. Thus, following this pioneering work, iodine has also been studied extensively and found to have significant enhancing effects to both enantioselectivity and reactivity in the Ir-catalyzed hydrogenation of imines [36,48] and of other closely-related substrate types, including enamines [89,90], quinoline derivatives [91][92][93][94][95], quinoxalines [96], and other heteroaromatics [97][98][99][100]. Representative examples of iodide compounds and iodine as effective additives in enantioselective imine hydrogenations are summarized in Table 1.…”
Section: Additive Effects and Mechanistic Perspectivesmentioning
confidence: 98%
“…[1] Asymmetric hydrogenation of N-heteroaromatic compounds is considered to be a difficult task due to aromatic resonance stability. Recent developments in asymmetric hydrogenation of N-heteroaromatic compounds, [2] such as 2-substituted quinolines [3][4][5][6][7][8][9][10][11][12][13][14][15] and quinoxalines [3h, k, 4c, f, 11, 16-22] (to give the 1,2,3,4-tetrahydroquinoline and 1,2,3,4-tetrahydroquinoxaline derivatives, respectively, in high enantioselectivity), pyridine derivatives, [3h, 4g, 23] pyr-roles, [24] imidazole, [25] oxazole, [25] and indoles, [26] have been remarkable. However, only a few mechanistic studies of the asymmetric hydrogenation of N-heteroaromatics have been reported.…”
Section: Introductionmentioning
confidence: 99%